PENGARUH LATIHAN PLANTAR FLEXOR TERHADAP KELENTUKAN PERGELANGAN KAKI PADA SISWA EKSTRAKURIKULER RENANG SMA 5 N PEKANBARU - M.Satria Maulana Maulana; Slamet '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem raised in this research is the effect of the training Plantar flexor exercise for flexibility foot Extention swimming ekstrakurikuler SMA 5 N pekanbaru,. The research aims to determine the effect of Plantar flexor exercise for flexibility foot Extention swimming ekstrakurikuler SMA 5 N pekanbaru.These research is pra experimental, the one group pretest – posttest design. The research was conducted in SMA 5 pekanbaru,The sample of this study of 10 people. Research data collected through the initial pretest and posttest with the flexibility foot extention test. The data were analyzed descriptive, then further research is done to test the hypothesis that has been asked in the problem, namely : there are plantar flexor exercise effect on  flexibility foot extention for swimming ekstrakurikuler SMA 5 N pekanbaru,. Based on t test analysis produces large thitung 15,15 and as much as 1,812 ttabel . Means thitung >  ttabel. It can be concluded that Ho denied and H1 accepted. It can be concluded that there is significant effect of the training Plantar flexor (X) and flexibility foot extention (Y)swimming ekstrakurikuler SMA 5 N  Pekanbaru. Keywords : Plantar flexor, flexibility foot extention.